Engine performance, emission and corrosion of biodiesel−bioethanol−diesel blends from Jatropha curcas‒ceiba pentandra mixed oil / Surya Dharma - Surya , Dharma (2018)
The increasing world population growth, energy crisis and environmental damage due to the use of fossil fuels are the main issues we face today, motivating many researchers to develop environmentally friendly, renewable and biodegradable fuels such as biodiesel. Biodiesel can be produced from various types of raw materials such as edible oil, non-edible oil, waste oil and animal fats. Numerous efforts have been made to increase the production and improve the properties of biodiesel by mixing several types of feedstock. The main objectives of this study are to optimize production, analyze engine performance and exhaust emissions, and investigate the corrosion of biodiesel produced from mixtures of crude J.curcas and C. pentandra oils. The selection of mixed compositions is based on the properties of crude oil mixtures. The biodiesel was produced using a two-step process, whereas the J. curcas and C. pentandra oil mixture was esterified with sulfuric acid (H2SO4) and the product of the esterification process was converted into methyl esters through alkali-catalysed transesterification. The opitmization of the methyl ester yield through transesterification process was through surface methodology based on Box-Behnken experimental design. The parameters such as methanol-to-oil ratio, agitation speed and concentration of the potassium hydroxide catalyst were evaluated in optimization biodiesel production. Based on the results, the optimum operating parameters for transesterification of the J50C50 oil mixture at 60 °C over a period of 2 hours were as follows: methanol-to-oil ratio: 30%, agitation speed: 1300 rpm and catalyst concentration: 0.5 wt.%. These optimum operating parameters gave the highest yield for the J50C50 biodiesel with a value of 93.33%. The physicochemical properties of the optimized J50C50 biodiesel fulfil the requirements given in the ASTM D6751 and EN 14214 standards. Experimental study was done regarding engine performance and exhaust emission using single cylinder direct injection engine. The fuel used was biodiesel-diesel and biodiesel-bioethanol-diesel fuel blends. Parameters that became the object of observation included brake specific fuel consumption, engine torque, brake power, exhaust gas temperature, brake thermal efficiency, CO, CO2, and NOx emissions, as well as smoke opacity. The results showed that the small content of biodiesel and bioethanol in the mixture had properties and performance close to diesel fuel, but significantly reduced the CO2 and smoke opacity. Analysis of corrosion behavior was done to analysee the effect of biodiesel and bioethanol on the degradation of machine components. A static immersion test method for 2000 hours was considered as appropriate to see the effect of mixed fuel on the corrosion of mild steel coupons. A series of tests was performed to see changes in mild steel coupons due to corrosion, such as scanning electron microscope, energy dispersive x-ray, fourier transform infrared, and properties testing. In conclusion, it is known that the rate of corrosion is influenced by the percentage of biodiesel and bioethanol content in the fuel mixture. The addition of biodiesel and bioethanol in a small percentage has a relatively similar corrosion rate with diesel fuel.